Education, social mobility and religious movements: A theory of the Islamic revival in Egypt - Christine Binzel; Jean-Paul Carvalho (Institute for the Study of Labor (IZA), 2013)
This paper examines the economic origins of the Islamic revival that took place in Egypt in the 1970-80s, and in Muslim societies more generally. We provide the first systematic evidence of a decline in social mobility among educated youth in Egypt. Developing a behavioral model of religion, we then characterize conditions under which a temporary decline in social mobility produces a large and long-lasting rise in religious participation. Religion in our model helps to cope with loss, which occurs when one's consumption falls below an expectations-based reference point. The model provides an explanation for why the educated middle class were in the vanguard of the Islamic revival. Rather than undermining religious belief and participation, our analysis suggests that economic development can make societies more prone to religious revivals.
Keywords: D10; D63; I24; J24; J62; O10; Z12; Z13; 330; Islamic revival; education; social mobility; inequality; social movements; Egypt